USERS PERCEPTION LEVEL ABOUT THE RISKS OF DOMESTIC PESTICIDE. (Fiep Bulletin - online, 2014)
Today with the advance of civilization, and the growing need for comfort and convenience, individuals are increasingly using household insecticides to control insects, which have toxic risk for humans. This study aims to determine the level of users' perception regarding the risk of using such substances. This is a descriptive, cross-sectional, quantitative study, in which 123 individuals agreed to participate by answering a questionnaire, which was used as a variable. The data, once compiled, are presented in tables and simple frequency graphs expressed in numbers and percentages. The ethical aspects were respected, in accordance with Resolution No. 196/96 (CNS - MS). The results show that 29.27% ??of the study subjects use household insecticide which is chosen by 43.09% for achieving various types of insects; 62.60% of interviewees believe that the product acts only on insects; 52.03% have never read the product label, but 49.59% reported having knowledge of the toxicity of the poison and when faced with the possibility of not using it 56.91% of subjects refused. In conclusion results suggest that the research subjects are aware of the risk of the use of household insecticides, recognize their toxicity, but believe that the benefit outweighs the risks they submit themselves to by using the product.
Keywords: Household insecticides; insect control; toxicology; Public health